DNA QR Code Using Internal Transcribed Spacer 1 (ITS1) Region of Commercial Cucumber Varieties (Cucumis sativus L.) - Turhadi, Turhadi; Padmana, I Made Dhena Radya; Azrianingsih, Rodiyati (Universitas Negeri Surabaya, 2025)
DNA Quick Response (DQR) is an accurate, efficient, fast, and cost-effective alternative to PCR-based or other sequencing methods. DQR is the method integrated seamlessly with digital systems. The DQR could be apply as effective approach to preventing seed counterfeiting, for example in cucumber. This study aimed to identify DNA barcodes based on the ITS1 region and develop DQR for commercial cucumber varieties in Indonesia. Two cucumber varieties, namely cv. Mars and cv. Makka were used. The genomic DNA was extracted using commercial DNA purification kit. The DQR for these two cucumber varieties were developed based on experimental data from the ITS1 region. The efficiency and characterization of ITS1 region were evaluated through homology analysis using BLAST-NCBI and DQR development. The DQR of cucumber cv. Mars and cv. Makka based on ITS1 region were successfully developed. The length of the ITS1 region encrypted in the QR code was 496 bp and 437 bp for cv. Mars and cv. Makka, respectively. The A-T and G-C proportions for cv. Mars were 45.2% and 54.8%, respectively, while for cv. Makka, the A-T and G-C proportions were 42.6% and 57.4%, respectively. Our findings are valuable for genetic labeling and authentication of horticultural crops, especially cucumber.